Adaptive strategies of Caribbean sponge holobionts beyond the mesophotic zone - Benoît Paix; Alexane Thivet; Celso Domingos; Özlem Erol; Niels van der Windt; Young H. Choi; Nicole J. de Voogd (Microbiome)
Abstract Background Marine sponges and their microbiomes function together as holobionts, playing essential roles in ecosystem dynamics and exhibiting remarkable adaptability across depth gradients. This study utilized a multi-omics approach, integrating microbiome and metabolome analyses, to investigate adaptive strategies in sponge holobionts inhabiting the mesophotic (80–125 m), upper-rariphotic (125–200 m), and lower-rariphotic (200–305 m) zones of Curaçao. We hypothesized that depth-related environmental factors drive distinct adaptive strategies, similar to patterns observed in fish and coral assemblages. Results Results revealed major differences in holometabolomes and microbial communities between Demospongiae and Hexactinellida sponges, reflecting class-specific adaptive strategies. Notably, phospholipid homeoviscous adaptation to temperature and pressure might emerge as a key mechanism in phosphorus metabolism. Adaptations in nitrogen metabolism were linked to diverse ammonia oxidizing archaea (AOA) symbionts, and dissolved organic matter cycling. Hexactinellid microbiomes exhibited intra-specific heterogeneity; however, species-specific associations with AOA symbionts such as Cenarchaeum and Nitrosopumilus were observed. Additionally, the lower-rariphotic hexactinellid holometabolomes highlighted the significance of the nested ecosystem concept through the identification of secondary metabolites produced by their associated fauna (aphrocallistins by zoanthids and xanthurenic acid by shrimp). Conclusions This study highlights the ecological significance of sponge holobionts in mesophotic and rariphotic ecosystems, revealing diverse adaptations to unique physicochemical conditions and biotic interactions. Video Abstract